Systematic review of the use of patient reported outcome measures in studies of electively-managed hand conditions - Lloyd-Hughes, H; Geoghegan, L; Rodrigues, J; Peters, M; Beard, D; Price, A; Jain, A (World Scientific Publishing, 2019)
Background: Electively-managed conditions account for over 100 000 inpatient surgeries a year in the English National Health Service alone, with further procedures in other regions of the UK, or performed on an outpatient basis. To quality assure this care and to conduct research, effective outcome measurement is critical. Traditional surgeon-centric outcome measures correlate poorly with hand function and are seldom important to patients. There has been an advent in the use of patient reported outcome measures (PROMs) in hand surgery although consensus of PROM choice appears to be lacking. This systematic review aimed to describe the use of relevant PROMs in clinical research of electively-managed hand conditions. Methods: A PRISMA-compliant methodology was used. A bespoke search strategy was developed in conjunction with a search strategist, and applied to Medline, EMBASE, CINAHL and PSYCHINFO from 1992 to June 2017. Pre-specified stepwise inclusion criteria were used to identify studies describing adult patients undergoing treatment for electively-managed hand conditions distal to the distal radius, with clinical outcomes measured using one or more PROMs. Results: Of 4554 results, 834 met inclusion criteria. PROMs identified included 9 disease-specific, 8 site-specific and 4 generic quality of life measures. Across all, the Disabilities of the Arm, Shoulder and Hand (DASH) was the most commonly used (overall frequency 41.0%). The most commonly reported disease-specific measure was the Boston Carpal Tunnel Questionnaire (overall frequency 23.0%). The most commonly reported generic quality of life of measure was the SF-36 (overall frequency 4%). Time-analysis demonstrated predominance of site-specific PROMs since the year 2000. Conclusions: Various PROMs have been used to study electively-managed hand conditions, with site-specific PROMs most popular. However, there appears to be limited consensus on choices. A future systematic evaluation of the published psychometric properties of identified PROMs may inform standardisation of measurement.